2013
DOI: 10.1002/clc.22143
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term Effect of Verapamil on Coronary No‐Reflow Associated With Percutaneous Coronary Intervention in Patients With Acute Coronary Syndrome: A Systematic Review and Meta‐analysis of Randomized Controlled Trials

Abstract: Background: To evaluate the clinical efficacy and safety of intracoronary verapamil injection in the prevention and treatment of coronary no-reflow after percutaneous coronary intervention (PCI). Hypothesis: Intracoronary verapamil injection may be beneficial in preventing no-reflow/slow-flow after PCI. Methods: We searched PubMed, Embase, and the Cochrane Central Register of Controlled Trials database. Randomized trials comparing the efficacy and safety of intracoronary verapamil infusion vs control in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Generally, the cause of a no-reflow phenomenon is likely multifactorial due to a combination of endothelial damage, platelet and fibrin embolization, vasospasm, and extracellular or intracellular tissue edema, ultimately leading to neutrophil plugs and platelet infiltration of myocardial tissue and microcirculation injuries [19]. At first, very selective and distal intracoronary or intravenous vasodilator such as adenosine [20,21], nicorandil [22], nitroprusside, nicardipine, or verapamil [23,24] is tried. Otherwise, epinephrine may be helpful [25,26].…”
Section: Violation Of Duty Of Carementioning
confidence: 99%
“…Generally, the cause of a no-reflow phenomenon is likely multifactorial due to a combination of endothelial damage, platelet and fibrin embolization, vasospasm, and extracellular or intracellular tissue edema, ultimately leading to neutrophil plugs and platelet infiltration of myocardial tissue and microcirculation injuries [19]. At first, very selective and distal intracoronary or intravenous vasodilator such as adenosine [20,21], nicorandil [22], nitroprusside, nicardipine, or verapamil [23,24] is tried. Otherwise, epinephrine may be helpful [25,26].…”
Section: Violation Of Duty Of Carementioning
confidence: 99%
“…The etiology of NRF is not yet fully understood, but it is assumed to be of multifactorial origin. Previous studies have identified several factors associated with NRF phenomenon, including plasma glucose, age, and pre‐PCI thrombus score . However, there is no screening tool to predict individual risk of developing NRF and to help health professionals make a decision on further intervention and select eligible patients into protocols focusing on mechanism and therapy of NRF.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of 108 patients with STEMI undergoing PPCI showed that a combination of intracoronary anisodipine (1 mg/5 ml) and diltiazem (2 mg/5 ml) reduced the rate of no-reflow/slow flow compared with diltiazem (2 mg/5 ml) alone [19]. A recent meta-analysis of seven randomized trials (539 patients with acute coronary syndromes undergoing PCI) showed that verapamil reduced the incidence of no-reflow, TIMI frame count, TIMI myocardial perfusion grade, and the 30-day wall motion index [61]. However, evidence on the use of these agents in the setting of PPCI remains limited.…”
Section: Statinsmentioning
confidence: 96%